THE ROLE OF AMINO ACID COMPOUNDS OF BLOOD PLASMA AND ITS INDICES IN THE DEVELOPMENT OF ARRHYTMIC COMPLICATIONS AND STRATTIFICATION OF CARDIOVASCULAR RISK IN PATIENTS WITH STABLE ISCHEAMIC HEART DISEASE ON THE BACKGROUND OF DIABETES MELLITUS TYPE 2 - J. Belikova (Bogomolets National Medical University, 2018)
Objective: to improve the prediction of arrhythmic complications, the stratification of cardiovascular risk (СVR) and to develop a differentiated approach to the appointment of metabolic cardiopotectors (MC) based on the study of the amino acid composition of blood (ASC). Object and methods of investigation The data of examination of 72 patients with stable ischemic heart disease (IHD) on the background of diabetes mellitus type 2 (DM 2) (38 men and 34 women, median ages -65,1 year) and 22 patients with stable coronary heart disease without violations of carbohydrate metabolism were analyzed. 20 amino acids (AMC) and the relationships between them were determined, in which AMCs were combined by a competitive mechanism of transport into the cell. According to the results of holter ECG monitoring, patients were divided into 2 groups: with and without arrhythmias of ischemic genesis (AIG) of high grades. Results For patients with IHD, against the background of DM 2, AIG is characterized by a reduced content of taurine (Tau) (by 38.4%), an increase in alanine (Ala) (by 21.42%), a total content of aromatic amino acids (ARA) (by 32.97%) in comparison with patients with prognostically indifferent arrhythmias. The risk of AIG is associated with Tau / Ala indices (<0.048) and aromatic amino acids/ metionin (ARA / Met) (> 34.41), regardless of the availability of demographic, anamnestic and clinico-laboratory risk predictors. Conclusion: Amino acid indices should be used as prognostic markers of AIG for the purpose of treatment of patients with IHD on the background of CD2. Tau and ARL are the most suitable for screening purposes, Тau / Ala (<0.048) and ARA / Met (> 34.41), it is more appropriate to use for the intended purpose of MC and as a control of treatment.